Experimental and numerical analysis of flexural test of unfilled glass fiber reinforced polymer composite laminate. (2018) - Chaudhary, S.K.; Singh, K.K.; Venugopal, R.
Abstract: Present investigation focus on flexural strength of unfilled glass fiber reinforced polymer laminate. In this work eight layers (0/90/±45/±45/0/90/0/90/±45/±45/0/90) of glass fiber/ epoxy laminates has been fabricated by hand lay-up and Vacuum bagging method. Flexural tests were peformed on designed fixture according to ASTM D790. Load was applied until first failure occurs by hounsfield tensometer with a capacity of 50 KN. Finite element analysis were also studied by Ansys software by APDL 14.5 model to validate experimental results. Structure and morphology of Fracture samples were also studied using Field emission scanning electron microscope (FE- SEM).